Modeling Debt And Equity Crowdfunding Based On Murabahah, Musharakah And Mudarabah: Trust And Awareness - Muhammad, Tijjani; bin Ngah, Assoc. Prof. Dr. Besar (IKONOMIKA, 2020)
Crowdfunding become one of the most effective alternatives for raising funds, although it is not a new phenomenon in developed and developing countries but seems to be new in Nigeria. As such, the study aims to propose Shariah framework that addresses conventional debt and equity crowdfunding, instead, using Murabaha as debt, Mudarabah and Musharakah as equity model and further measure the level of awareness and trust towards behavioural intention towards crowdfunding in Northern Nigeria. The sample was collected from 2730 purposively selected and used Structural Equation Modeling (SEM) for data analysis. Findings, revealed that the proposed structural framework of crowdfunding proved to enhance entrepreneur vision for raising investment fund based on Shariah-compliant in Northern Nigeria. Further indicates, lack of awareness and inappropriate use of internet platform resulted in perceived entirely irrelevant investment opportunities and developed fair to invest online.  Practical implications: The paper provides awareness and trust on how to improve debt and equity-based crowdfunding for a fundraiser and successful funding a business structure based on Shariah compliant. Originality/Value: the study makes significant contribution towards propose Shariah framework of crowdfunding in Nigeria, and it provides awareness and trust to Nigerian Muslims entrepreneurs as in line with Shariah-compliant.JEL Classification: E4, O31, O35